Fectores biosociales que influyen en el nivel de depresión de pacientes con Insuficiencia Renal Crónica Hemodializados, Clínica Internacional del Riñón - López Cabrera, María Luisa (2015)
Descriptive correlational cross-sectional study was conducted during the months of April to July 2015, at the International Kidney Clinic, in order to determine the influence of Biosocial factors: age, sex, level of education, marital status on the level of depression in hemodialysis patients with chronic renal failure. The characteristics of the investigation was used as a conceptual framework defining levels of depression cited by Kaplan (2006); and Biosocial factors described by DUGAS ( 2000 ). The sample consisted of 54 adult patients (20 to more) hemodialysis that met the requirements for research. A self-administered questionnaire survey included Zung depression questionnaire and biosocial factors Rodriguez (2003 ) .For statistical analysis test criteria of independence Chi square ( X2 ) .The results was used was applied shows that there is an influence statistically significant between the biosocial factors: age , sex , level of education and the level of depression hemodialysate patient ; however as the civil status of the patient factor hemodialysate no significant statistical influence the level of depression, according to the test criteria of independence Chi – square.